A Study How Do Community Care Providers Collaborate With Local Authorities and Emergency Response Teams During A Disaster Situation: A Literature Review - Riwayanti, Adinda Agus; Hutami, Citra Kirana; Azzahro, Nur Fauziah; Usraturrahmah, Usraturrahmah (Tarqabin Nusantara Group, 2024)
Introduction: The Unitary State of the Republic of Indonesia is a country located in a disaster-prone area due to geographical, geological, hydrological and demographic conditions that allow natural, non-natural and social disasters to occur. Therefore, the government passed Law Number 24 of 2007 concerning Disaster Management to disseminate information to the public regarding disaster management, provide protection to the community from every threat of disaster and ensure the implementation of disaster management. Methods: A systematic search was conducted against the Cochrane Database of Reviews, Google Scholar, PubMed, Scopus, Embase, and Web of Science. The keywords in this research are